Frequency and Related Factors of Depressive Symptom Elders Who Live in a Residential Home in Istanbul - KARAVUŞ, MELDA; LÜLECİ, NİMET EMEL (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective:The elderly population, defined as >= 65 years old, is increasing with time in society. Depressive symptoms in old age lead to worsening of physical and cognitive abilities. This study investigated the prevalence of depressive symptoms in elderly people living in a residential home in Istanbul and factors affecting this indication. Methods:The study was conducted in a descriptive and cross-sectional manner. The questionnaire, which included sociodemographic questions and inquiries on factors affecting depression, Geriatric Depression Scale Short Form-15 (GDS-15), and Mini-Mental test, was administered to 77 elderly people. Results:Twenty-nine of the participants were females and 48 were males, with a mean age of 75.9 +/- 8.2 years. The mean GDS-15 score of the elderly was 4.04 +/- 3.42. Concerns regarding leaving the residential home, low telephone call frequency, persistent physical illness, and inability to complete self-care activities were significantly associated with depressive symptoms. Conclusion:Depressive symptoms are common in the elderly living in residential homes. This occurrence is closely related to social support and health status. Further studies are warranted to determine if factors associated with such symptoms are risk factors for depression.
Keywords: Social Support; Depression; Self Care; Health Status; OLDER-PEOPLE; SUPPORT